Structural, morphological, thermal and electrochemical characteristics of chitosan: praseodymium triflate based solid polymer electrolytes - Alves, Raquel Diana Carneiro (2019)
Praseodymium triflate (PrTrif) is used as a dopant for the synthesis of new solid polymer electrolytes (SPEs) based on chitosan. Our focus is to study the influence of the salt amount on the electrochemical, morphological, and thermal properties of these new SPEs. Therefore, all the samples are analyzed by complex impedance spectroscopy to determine their ionic conductivity values, X-ray diffraction (XRD), scanning electron microscopy (SEM), thermogravimetric analysis (TGA), and differential scanning calorimetry (DSC) to establish their structural and thermal properties. Additionally, the samples? luminescent properties are also evaluated. As a result, we observe that the sample with lower salt amount is less crystalline, which probably reflects on the ionic conductivity increase. The SPE with 20.30wt% of PrTrif showed the highest ionic conductivity of 2.38 ? 10(?6) S cm(?1) at 90? C. Surface featuring of the films, reveals the formation of some irregularities, typically observed in semi-crystalline polymer electrolytes. The characteristic luminescence of Pr3+ ion in the visible spectral region is impaired by overlap with the strong emission of the chitosan polymer host. In the infrared region, the characteristic emissions in the range 900?1100 nm (P-3(0)?(1)G(4) and D-1(2)?F-3(4)) are observed under excitation at 590 nm (H-3(4)?D-1(2)) where the absorption by the chitosan host is less pronounced. The results presented here suggest that these materials are promising and may find application in practical electrochemical devices.